2014
DOI: 10.1007/s11130-014-0430-0
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Antioxidant Activity, Total Phenolic and Flavonoid Contents by Optimizing the Germination Conditions of Amaranth Seeds

Abstract: The aim of this study was to optimize the germination conditions of amaranth seeds that would maximize the antioxidant activity (AoxA), total phenolic (TPC), and flavonoid (TFC) contents. To optimize the germination bioprocess, response surface methodology was applied over three response variables (AoxA, TPC, TFC). A central composite rotable experimental design with two factors [germination temperature (GT), 20-45 ºC; germination time (Gt), 14-120 h] in five levels was used; 13 treatments were generated. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
41
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 28 publications
9
41
0
4
Order By: Relevance
“…As for germinated seeds, our results showed that 4-day-old sprouts have a significantly higher AC than seeds, associated to a strong PC increase. These results are in accordance with some literature data, showing a remarkable increase of both AC and PC (in particular, protocatechuic, vanillic and caffeic acids, as well as kaempferol and quercetin glycosides) after germination of seeds of quinoa (Paśko et al, 2009;Alvarez-Jubete et al, 2010;Carciochi et al, 2016) and of other species (Cevallos-Casals and Cisneros-Zevallos, 2010;Pająk et al, 2014;Perales-Sánchez et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As for germinated seeds, our results showed that 4-day-old sprouts have a significantly higher AC than seeds, associated to a strong PC increase. These results are in accordance with some literature data, showing a remarkable increase of both AC and PC (in particular, protocatechuic, vanillic and caffeic acids, as well as kaempferol and quercetin glycosides) after germination of seeds of quinoa (Paśko et al, 2009;Alvarez-Jubete et al, 2010;Carciochi et al, 2016) and of other species (Cevallos-Casals and Cisneros-Zevallos, 2010;Pająk et al, 2014;Perales-Sánchez et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Some investigations have been also performed on sprouts from other edible seed species (Paśko et al, 2009;Cevallos-Casals and Cisneros-Zevallos, 2010;Pająk et al, 2014;Perales-Sánchez et al, 2014). Most of these studies are focused on the evaluation of phenolic content (PC) and in vitro antioxidant capacity (AC) of sprouts obtained from different seed species in different germination conditions.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative reason for the increase in protein content was explained as being due to release of free amino acid as a result of enzymatic hydrolysis, causing synthesis of more proteins . Decrease in dry matter due to respiration and germination could also increase the protein level of the seed after germination …”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Paśko et al . () found that antioxidant activity measured by DPPH radical scavenging assay was maximal after germination of quinoa at 20 °C for 144 h. Moreover, an increase in antioxidant activity with higher germination temperature and time has been also observed in other pseudocereals such as amaranth (Perales‐Sánchez et al ., ; Paucar‐Menacho et al ., ). The increase in antioxidant activity in sprouted quinoa can be attributed to the accumulation of phenolic compounds and to the release of bound phenolics during germination, as it has been reported for cereals and legumes (Tang et al ., ).…”
Section: Resultsmentioning
confidence: 99%